Expression of Epithelial-Mesenchymal Transition-related Factors in Adherent Placenta. (November 2015) - Shirakawa, Tokuro; Miyahara, Yoshiya; Tanimura, Kenji; Morita, Hiroki; Kawakami, Fumi; Itoh, Tomoo; Yamada, Hideto
Abstract : Epithelial-mesenchymal transition is a key process influencing cancer progression and metastasis. The purpose of this study was to investigate the expression of epithelial-mesenchymal transition-related factors in chorionic villi and decidual cells in adherent placenta. The current study included 19 patients diagnosed with adherent placenta after hysterectomy. The expression of E-cadherin, Vimentin, Snail, and transforming growth factor-β in placental tissues was analyzed by immunohistochemical staining. Immunostaining intensity was semiquantitatively evaluated using the HSCORE algorithm. In the chorionic villi of the invasive part (placenta with invasion into myometrium), E-cadherin expression was significantly lower than that in the noninvasive part (placenta with no invasion). In the decidual cells of the invasive part, expression of transforming growth factor-β and Snail significantly increased. These results suggest that epithelial-mesenchymal transition may contribute to excessive trophoblast invasion into the myometrium in adherent placenta.